Pemanfaatan Ubi Kayu Sebagai Produk Olahan untuk Meningkatkan Pendapatan di Desa Mamben Baru Kecamatan Wanasaba Lombok Timur - Faresta, Rangga Alif; Safana, Mega; Raenaldi, Raenaldi; Yuraeda, Mufidah; Kamal, Eta Lestari; Faroby, Muhammad Adzy; Zamzami, Zamzami; Safitri, Ivo Yolanda; Fakhriyah, Novita Nurul; Sofy, Peny Aulia (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2021)
The potential of East Lombok in agriculture is very large. One of them is Mamben Baru Village, Wanasaba District. This village has abundant cassava potential, especially when the harvest season arrives, which is April to May. However, the problem that arises is that the local community is not yet skilled in processing cassava into products of high economic value. Therefore, that this program aims to provide training in the manufacture of processed cassava-based products. The stages in this empowerment activity start from the preparation stage, the activity implementation stage, and the product evaluation stage. The results obtained in this empowerment activity are the creation of processed products that can help the community of Mamben Baru Village in developing processed cassava products into sweet potato chips. So that the formation of people who are skilled in processing cassava into processed products that have their own uniqueness with variants of flavors offered and have more selling power. This empowerment program provides benefits that can improve the skills of the Wanasaba Village community